(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Reflecting on mandatory or only recommended vaccinations in the perspective of constitutional law allows to highlight the problems of balancing the fundamental rights which are relevant in this regard (the right to health, the freedom of self-determination in therapeutic choices, the right to education, the duties and the rights of parental care). Secondly these issues raised by vaccination treatments allow to reflect on a whole series of further broader profiles, which involve the fundamental principles of the Italian form of state and government and the complex relationship between scientific achievements (and their evolution), law and constitutional judgment.